2001
DOI: 10.1097/00006199-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity in Chronic Obstructive Pulmonary Disease

Abstract: Accelerometer measurement of functional performance was most significantly related to walking abilities. This methodology represents a novel approach to measuring an important dimension of functional status not previously well quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
99
2
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 28 publications
12
99
2
7
Order By: Relevance
“…It is also noticed that this classification might not be sustainable for older adults and those living with chronic diseases. There are a few studies that measured daily physical activity in patients with COPD with an accelerometer [51][52][53] and with a pedometer [31]. Patients in the latter study took approximately 3700 steps/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noticed that this classification might not be sustainable for older adults and those living with chronic diseases. There are a few studies that measured daily physical activity in patients with COPD with an accelerometer [51][52][53] and with a pedometer [31]. Patients in the latter study took approximately 3700 steps/day.…”
Section: Discussionmentioning
confidence: 99%
“…By incorporating these activities during pulmonary rehabilitation, daily physical activity levels may remain higher after rehabilitation and the benefits of rehabilitation may last longer. The Dutch Norms for Healthy Physical Activity (DNHPA), which is derived from the www.elsevier.com/locate/pateducou Patient Education and Counseling 61 (2006) [48][49][50][51][52][53][54][55] norms of the American College of Sports Medicine (ACSM) [9][10][11], serve as reference for the effects of lifestyle physical activities on health.…”
Section: Introductionmentioning
confidence: 99%
“…Postprint available at: http://www.zora.uzh.ch Similarly, ambulatory activity monitoring did not correlate significantly with self-reported functional status in patients with chronic obstructive pulmonary disease. [20] To the best of our knowledge, only one previous report has investigated the relationship between ambulatory step activity monitoring, self-reported physical functioning and the 6-minute standardized walking test in cancer patients.[28] There was moderate agreement between the 7-Day Physical Activity Recall and the accelerometer with longitudinal serial correlation coefficients of 0.54 (baseline), 0.24 (year 1), and 0.53 (year 2), all p-values <0.01.To summarize, the association observed between self-reported physical functioning, standardized timed walking and the outputs of ambulatory step activity varies from none to almost perfect in studies of various chronic disease populations. Only one study has investigated this issue in cancer patients, and none among HSCT patients.…”
mentioning
confidence: 99%
“…Postprint available at: http://www.zora.uzh.ch Similarly, ambulatory activity monitoring did not correlate significantly with self-reported functional status in patients with chronic obstructive pulmonary disease. [20] To the best of our knowledge, only one previous report has investigated the relationship between ambulatory step activity monitoring, self-reported physical functioning and the 6-minute standardized walking test in cancer patients.…”
mentioning
confidence: 99%
“…In the study by Baghai-Ravary et al 64 fatigue remained the only factor significantly associated with time spent outdoors, suggesting fatigue is considerable restrictor of physical activity. One study found fatigue to be one of the correlates to physical activity measured with an activity monitor 53 while another study did not found a relation between fatigue and physical activity measured with an accelerometer 49 . To elucidate the pathway to low PA in COPD we need to understand which factors are important contributors to PA.…”
Section: Fatiguementioning
confidence: 99%